Phosphor‐converted white light from blue‐emitting InGaN microrod LEDs. Issue 6 (8th February 2016) - Schimpke, Tilman; Mandl, Martin; Stoll, Ion; Pohl‐Klein, Bianca; Bichler, Daniel; Zwaschka, Franz; Strube‐Knyrim, Johanna; Huckenbeck, Barbara; Max, Benjamin; Müller, Marcus; Veit, Peter; Bertram, Frank; et al.
Abstract : A uniform array of gallium nitride core‐shell microrod (MR) light‐emitting diode (LED) structures was grown by metalorganic vapor phase epitaxy. Defects and the quantum well (QW) luminescence in an individual rod were investigated by scanning tunneling electron microscopy (STEM) and STEM cathodoluminescence. Luminescence with different wavelength was detected from the quantum wells on the semipolar tip facets and the nonpolar sidewalls of the MRs. Furthermore, the MR array is processed into LED chips. The electro‐optical characteristics of the devices are analyzed. Two separate emission bands are distinguished, which are attributed to the QWs on the semipolar tip facets and the nonpolar sidewalls, respectively. To obtain white LEDs, micrograin phosphors were developed which fit in between individual MRs. By using electrophoretic particle deposition, these phosphors are deposited onto the MR LED chips. Color coordinates, color temperature, and device efficiency are evaluated. Blue (top) and phosphor‐converted white (bottom) microrod LEDs on 4″ wafer.